2001
DOI: 10.1007/s002280100290
|View full text |Cite
|
Sign up to set email alerts
|

Organising evidence on QT prolongation and occurrence of Torsades de Pointes with non-antiarrhythmic drugs: a call for consensus

Abstract: This list should be considered as a starting point to call for consensus on: (1) the criteria used to generate the list, (2) possible ways to implement the use of this list as a quick reference for clinicians, for instance by providing a "proarrhythmic score" for each drug, and (3) inclusion/exclusion of a given agent into the list on the basis of evidence that may not be available to us.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
109
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 162 publications
(110 citation statements)
references
References 0 publications
1
109
0
Order By: Relevance
“…14 These differences in the electrophysiological profiles of these drugs might explain their clinically described antiarrhythmic and proarrhythmic effects. 1,2,12,13 …”
Section: Effects On the Terminal Repolarization Phasementioning
confidence: 99%
“…14 These differences in the electrophysiological profiles of these drugs might explain their clinically described antiarrhythmic and proarrhythmic effects. 1,2,12,13 …”
Section: Effects On the Terminal Repolarization Phasementioning
confidence: 99%
“…Considerable evidence has accrued that a variety of noncardiac drugs may prolong the QT interval of the surface electrocardiogram, which represents ventricular depolarization and repolarization, imparting an increased risk of developing a potentially fatal cardiac arrhythmia known as torades de pointes (TdP) (De Ponti et al, 2001). This has stimulated intense discussions and focused attention on methodological issues involved in the cardiac risk-benefit assessment of noncardiac pharmaceuticals, including antimicrobial agents, which has resulted in withdrawals of approved antibiotics such as grepafloxacin.…”
mentioning
confidence: 99%
“…The reason for this was that a correction formula that adequately corrected QT intervals was used in the current study. Drug-induced QT prolongation is relatively common in clinical practice (De Ponti et al, 2001;Redfern et al, 2003;Ozkanlar et al, 2005b). It has been reported that sparfloxacin and grepafloxacin can prolong the QT interval to cause lethal ventricular arrhythmias (Bertino and Fish, 2000;Frothingham, 2001;Owens, 2001).…”
Section: Discussionmentioning
confidence: 99%